Pengaruh Trust In Brand Dan Customer Satisfaction Terhadap Loyalitas Pelanggan PT Mandiri Bangun Berkarya di Jakarta - Indi Prihatini , Indi Prihatini; Achmad Jaelani, Achmad Jaelani; Henny Risnawati, Henny Risnawati (LPPM Swadaya Institute of Business and Communication, 2024)
The aim of this research is to find out the impact of trust in the brand and customer satisfaction on customer loyalty at PT Mandiri Bangun Berkarya in Jakarta. As for the method used, it's a quantitative method. Data collection method using the questionnaire method. The free variables are trust in the brand and customer satisfaction, and the bound variable is customer loyalty at PT Mandiri Bangun Berkarya in Jakarta. All statements are stated to be valid, reliable, and normally distributed. Based on the tests carried out, the results of this study show that the trust in brand variable (X1) has a Cronbach's alpha value of 0.855 and the customer satisfaction variable (X2) has a value of 0.849. Trust in brand and client satisfaction have a strong relationship to customer loyalty, as seen at an R square of 0.821, which shows the independent variable consisting of trust in brand and customer satisfaction can be explained by customer loyalty of 82.1% and 17.9%, respectively, which are influenced by other variables not studied in this study.